Gneiss Domes in Orogeny 2004
DOI: 10.1130/0-8137-2380-9.35
|View full text |Cite
|
Sign up to set email alerts
|

The exhumation of gneiss domes in bivergent wedges: Geometrical concepts and examples from the Himalayan syntaxes

Abstract: Gneiss domes are typically bounded by shear zones that accommodated differential exhumation relative to their surrounding host rocks. Consideration of possible structural geometries shows that two arrangements are particularly effective at exhuming deep crustal rocks. One consists of sub-parallel dipping shear zones, where an upper normal shear zone overlies a lower reverse shear zone. The other is a bivergent wedge, bounded by conjugate reverse shear zones, where vigorous erosion is required for substantial e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The cross-section interpretation in Figure 15 shows that the older rock (metamorphic rock) is on top of the younger rock (carbonate of Oyo Formation) due to thrust fault growth. The structural geology analysis in the study shows a stacking system called an imbrication thrust stack (Whittington, 2004). This phenomenon causes the exhumation and uplifting of West Jiwo Hills (Figure 16).…”
Section: Sub-surface Interpretationmentioning
confidence: 87%
See 1 more Smart Citation
“…The cross-section interpretation in Figure 15 shows that the older rock (metamorphic rock) is on top of the younger rock (carbonate of Oyo Formation) due to thrust fault growth. The structural geology analysis in the study shows a stacking system called an imbrication thrust stack (Whittington, 2004). This phenomenon causes the exhumation and uplifting of West Jiwo Hills (Figure 16).…”
Section: Sub-surface Interpretationmentioning
confidence: 87%
“…Figure16. Modified imbricate thrust stack model byWhittington (2004) as a suggested model to explain the exhumation of West Jiwo Hills, Bayat. This model also proves that Jombor Swamp was a piggyback product of thrust fault.…”
mentioning
confidence: 99%
“…Various mechanisms have been proposed for the dynamic causes and kinematic development of gneiss domes by Yin (2004) and Whittington (2004). The latter suggested that bivergent wedges may develop by two conjugate shear zones, that on a smaller scale are known as "pop-up" or "flower" structures, in a compressional deformation regime.…”
Section: Movement Of Faults and The Present Geodynamic Modelmentioning
confidence: 98%
“…2) (Getty and Gromet, 1992;Amato et al, 1994;Whittington, 2004). The Tutak gneiss dome provides a structural window for studying deformation and polyphase orogenic events in the Zagros Orogenic Belt of Iran.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation